Perovskite solar cell and preparation method thereof

CN123021889APending Publication Date: 2026-10-30TONGWEI SOLAR ENERGY (CHENGDU) CO LID
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611269859.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

SnO2因高电子迁移率(>20 cm2/V·s)、低温加工性和适宜能级(导带-4.0 eV)成为主流电子传输层材料,但SnO2作为电子传输层材料仍存在三大瓶颈问题:(1)缺陷态密度高:未掺杂SnO2中氧空位(Vo++)和锡空位(Vsn4-)容易导致界面复合,损失开路电压(Voc);(2)能级失配:SnO2导带与钙钛矿(如MAPbI3, -3.9 eV)存在>0.1 eV偏移,会阻碍电子提取;(3)湿热稳定性差:ETL/钙钛矿界面离子迁移会加速器件降解

Benefits of technology

(1)缺陷修复-电导增强协同:Mg2+填补Sn空位,使氧空位形成能上升,缺陷密度降低;F-替代O2-提供自由电子,费米能级上移,载流子浓度提升,电子迁移率提升;Mg可以抑制F引起的晶格膨胀,晶格畸变能降低,无裂纹产生;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021889A_ABST
    Figure CN123021889A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite solar cell and a preparation method thereof, and relates to the technical field of photovoltaics. The perovskite solar cell is prepared by creatively adopting a magnesium and fluorine co-doped tin oxide film as an electron transport layer (ETL) of the perovskite solar cell, so that the conductivity can be improved and defects can be passivated, the annealing temperature can be reduced to meet the application requirements of a flexible device, and the interface stability can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic technology, and more specifically, to a perovskite solar cell and its fabrication method. Background Technology

[0002] Perovskite solar cells (PSCs) have become a hot topic in photovoltaic research due to their high efficiency (>27%) and low-cost solution processability. The electron transport layer (ETL) plays a crucial role in perovskite crystallization, extracting electrons and blocking holes. SnO2, with its high electron mobility (>20 cm⁻¹), is particularly valuable for this purpose. 2 SnO2 has become the mainstream electron transport layer material due to its low temperature processability and suitable energy level (conduction band -4.0 eV), but SnO2 still has three major bottleneck problems as an electron transport layer material: (1) High defect state density: The oxygen vacancy (V / s) in undoped SnO2 is high. o ++ ) and tin vacancies (V sn 4- (1) It is easy to cause interface recombination and loss of open circuit voltage (Voc); (2) Energy level mismatch: SnO2 conduction band and perovskite (such as MAPbI3, -3.9 eV) have a shift of >0.1 eV, which will hinder electron extraction; (3) Poor wet and hot stability: Ion migration at the ETL / perovskite interface will accelerate device degradation.

[0003] To improve the performance of SnO2, current research mainly adopts single-element doping strategies, but all of them have significant limitations: (1) F - Doping: via F - Replace O 2- Increasing the carrier concentration increases the conductivity by 300%, but the oxygen vacancy concentration increases by 30%, resulting in an efficiency decay rate of >15% under long-term illumination; (2) Mg 2+ Doping: using Mg 2+ (0.72 Å) filled Sn 4+ Vacancies (0.69 Å) suppress lattice distortion, reducing the defect density to 9.5 × 10⁻⁶. 17 cm -3 However, its electron mobility is only 15.3 cm⁻¹. 2 / V·s, the fill factor (FF) is difficult to exceed 80%; (3)W 6+ Doping: High-valence doping improves electrical conductivity, but the annealing temperature needs to be >200°C, which is not compatible with flexible PET substrates (glass transition temperature ~150°C).

[0004] The main technical problems with SnO2 doping technology are as follows: (1) Intrinsic defects (oxygen vacancies, tin vacancies) in SnO2 ETL lead to severe interfacial recombination; (2) Single-element doping cannot simultaneously improve conductivity and passivate defects; (3) High-temperature processes (>180℃) will limit the application of flexible devices; (4) Ion migration at the ETL / perovskite interface accelerates device decay.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a perovskite solar cell and its fabrication method, which aims to balance the improvement of conductivity and defect passivation, reduce the annealing temperature to meet the application requirements of flexible devices, and improve interface stability.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a perovskite solar cell, comprising an electron transport layer, wherein the electron transport layer is a magnesium and fluorine co-doped tin oxide thin film.

[0008] In an optional embodiment, the magnesium and fluorine co-doped tin oxide film has the chemical formula Sn. 1-x Mg x O 2-y F y Where 0.005≤x≤0.04, 0.01≤y≤0.06, and the molar ratio of Mg to F is 1:(1.5-3.0).

[0009] In an optional embodiment, it further includes a first electrode, a perovskite light-absorbing layer, a hole transport layer and a second electrode, and the first electrode, the electron transport layer, the perovskite light-absorbing layer, the hole transport layer and the second electrode are stacked sequentially to form a stacked structure. Preferably, a buffer layer with the chemical formula MgF is further included between the perovskite light-absorbing layer and the tin oxide film. x O 2-x ; Preferably, in the tin oxide film, Mg 2+ Filling Sn vacancies increases the oxygen vacancy formation energy from 1.6–2.0 eV to 2.5–3.5 eV; F - Replace O 2- Provides free electrons, with an electron mobility of up to 30 cm⁻¹ 2 / V·s or more; Preferably, Mg inhibits lattice expansion caused by F, the lattice distortion energy is <0.05 eV, and no cracks are generated; Preferably, co-doping shifts the SnO2 conduction band from -4.03~-3.98 eV to -3.95~-3.90 eV, resulting in a mismatch of <0.02 eV with the perovskite energy level and increasing the open-circuit voltage Voc to 1.15~1.20 V.

[0010] In an optional embodiment, the material of the first electrode is selected from at least one of ITO, FTO and AZO; And / or, the material of the perovskite light-absorbing layer is selected from ABX3 and A2A. n-1 B n X 3n+1 At least one of the following; wherein 1≤n≤10, A is selected from at least one of Cs, MA and FA; B is selected from at least one of Pb and Sn; X is a halogen element; And / or, the material of the hole transport layer is selected from at least one of NiOx, V2O5 and MoO3; And / or, the material of the second electrode is selected from at least one of Ag, Au and Cu; And / or, the thicknesses of the first electrode, the electron transport layer, the perovskite light-absorbing layer, the hole transport layer, and the second electrode are, respectively, 100nm-200nm, 10nm-50nm, 300nm-800nm, 50nm-100nm, and 200nm-400nm.

[0011] Secondly, the present invention provides a method for preparing any of the foregoing embodiments of a perovskite solar cell, comprising: Preparation of precursor solution: A tin salt, solvent, organomagnesium source, fluorine source and alcohol stabilizer are mixed and reacted to obtain a precursor solution; Preparation of electron transport layer: The precursor solution is coated on the first electrode and then annealed.

[0012] In an optional embodiment, the process of preparing the precursor solution includes: mixing a tin salt and a solvent, then mixing it with an organomagnesium source and sonicating it until completely dissolved to obtain a mixed solution; adding an aqueous solution of a fluorine source dropwise to the mixed solution, and after the addition is complete, adding an alcohol stabilizer, reacting for 1-5 hours, and then filtering. And / or, spin-coating the precursor solution onto the first electrode, followed by annealing, with the annealing temperature controlled at 120℃-150℃ and the annealing time at 20min-60min.

[0013] In an optional embodiment, the concentration of tin in the mixed solution is 0.05 mol / L-0.2 mol / L, and the concentration of magnesium is 0.0005 mol / L-0.008 mol / L; the concentration of fluorine in the added aqueous solution of the fluorine source is 0.1 mol / L-1 mol / L, and the volume ratio of the mixed solution to the aqueous solution of the fluorine source is 1:(0.01-0.1). And / or, the tin salt is selected from at least one of tin chloride, tin nitrate, tin sulfate, and tin acetylacetonate; And / or, the organic magnesium source is selected from at least one of Mg(CH3COO)2, magnesium acetylacetonate, magnesium citrate and magnesium oxalate; and / or, the fluorine source is selected from at least one of NH4F, ammonium bifluoride and tetrabutylammonium fluoride; And / or, the alcohol stabilizer is selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, diethylene glycol monomethyl ether and propylene glycol methyl ether, and the molar ratio of tin salt to alcohol stabilizer is 1:(0.5-2).

[0014] In an optional embodiment, during the mixing process with the solvent, the mixing temperature is controlled at 35℃-50℃, and the stirring time is 0.5h-3.0h; And / or, the solvent is a mixture of water and ethanol, with a volume ratio of water to ethanol of 1:(1.5-4). And / or, during the ultrasonic treatment, the ultrasonic temperature is controlled at 50℃-70℃; And / or, the dropping rate of the aqueous solution of the fluorine source is 0.5 mL / min to 1.5 mL / min; And / or, the annealing process is carried out in an air atmosphere, with the heating rate controlled at 4℃ / s-6℃ / s.

[0015] In an optional embodiment, the method further includes: sequentially fabricating a perovskite light-absorbing layer, a hole transport layer, and a second electrode on the electron transport layer to form a stacked structure.

[0016] In an optional embodiment, the process of preparing the perovskite light-absorbing layer includes: preparing materials according to the composition of the perovskite light-absorbing layer and mixing and dissolving them with a solvent to form a perovskite precursor solution; coating the perovskite precursor solution onto the electron transport layer; adding an anti-solvent during spin coating; and then annealing at high temperature, controlling the annealing temperature to be 100℃-120℃ and the annealing time to be 15min-30min. And / or, a hole transport layer is deposited using PVD; And / or, the second electrode is prepared by vapor deposition.

[0017] The present invention has the following beneficial effects: The present invention creatively uses magnesium and fluorine co-doped tin oxide thin film as the electron transport layer (ETL) of perovskite solar cells, which can balance the improvement of conductivity and defect passivation, reduce the annealing temperature to meet the application requirements of flexible devices, and improve interface stability.

[0018] Specifically, the electronic transport layer (ETL) provided in this embodiment of the invention has the following advantages: (1) Defect repair-conductivity enhancement synergy: Mg 2+ Filling Sn vacancies increases the oxygen vacancy formation energy and reduces the defect density; F - Replace O 2- Providing free electrons shifts the Fermi level upward, increasing carrier concentration and electron mobility; Mg can suppress lattice expansion caused by F, reducing lattice distortion energy and preventing crack formation. (2) Precise control of energy level: Co-doping causes the SnO2 conduction band to shift upward, resulting in a mismatch with the perovskite energy level and an increase in Voc; (3) Low-temperature process compatibility: The sol-gel method can form a dense film by annealing at low temperature, which can meet the application requirements of flexible devices; (4) Interface stability: In-situ generation of interface buffer layer MgF x O 2-x F - Enrichment Interface → I - Pb is fixed by Mg-O-Pb due to Coulombic repulsion. 2+ It inhibits ion migration. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic diagram of a perovskite solar cell structure. Figure 2 This is a diagram of the bandgap structure. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0022] Existing electron transport layers cannot simultaneously satisfy: (1) synergistic optimization of bulk defects and interface energy levels; (2) low-temperature film deposition process ≤150°C; and (3) long-term stability to suppress ion migration. To address the above problems, this invention improves the electron transport layer material for perovskite solar cells. The improved electron transport layer can balance improved conductivity and defect passivation, can reduce the annealing temperature to meet the application requirements of flexible devices, and can also improve interface stability.

[0023] This invention provides a perovskite solar cell, including an electron transport layer, which is a magnesium and fluorine co-doped tin oxide thin film, wherein Mg is simultaneously doped in the tin oxide ETL system. 2+ With F - .

[0024] It should be noted that Mg is also doped in the tin oxide ETL system. 2+ With F - It has the following advantages: (1) Defect repair-conductivity enhancement synergy: Mg 2+ Filling Sn vacancies increases the oxygen vacancy formation energy from 1.8 eV (1.6~2.0 eV) to 3.0 eV (2.5~3.5 eV), reducing the defect density; F - Replace O 2- The introduction of free electrons shifts the Fermi level upward, increases carrier concentration, and achieves an electron mobility of 30 cm⁻¹. 2 / V·s or more, specifically 32.8 cm 2 / V·s; Mg inhibits lattice expansion caused by F, lattice distortion energy <0.05 eV, and no cracks are generated; (2) Precise energy level control: Co-doping shifts the SnO2 conduction band from -4.0 eV (-4.03~-3.98 eV) to -3.92 eV (-3.95~-3.90 eV), with a mismatch of <0.02 eV with the perovskite energy level, and the open circuit voltage Voc is increased to 1.18 V (1.15~1.20 V); (3) Low temperature process compatibility: The sol-gel method can form a dense film by annealing at 150℃, which is much lower than the requirement of 180-200℃; (4) Interface stability: In-situ generation of interface buffer layer MgF x O 2-x F - Enrichment Interface → I - Pb is fixed by Mg-O-Pb due to Coulombic repulsion. 2+ It inhibits ion migration.

[0025] In some embodiments, the chemical formula of the magnesium and fluorine co-doped tin oxide film is Sn. 1-x Mgx O 2-y F y Where 0.005≤x≤0.04, 0.01≤y≤0.06, and the molar ratio of Mg to F is 1:(1.5-3.0). Preferably, x=0.015, y=0.03. By adjusting the doping ratio of magnesium and fluorine, the defect passivation effect can be further improved, while the conductivity can be increased. Specifically, the value of x can be 0.005, 0.008, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, etc.; the value of y can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, etc.; and the molar ratio of Mg to F can be 1:1.5, 1:2.0, 1:2.5, 1:3.0, etc.

[0026] Embodiments of the present invention can generate an interface buffer layer MgF in situ. x O 2-x The buffer layer is self-assembling, requiring no vacuum equipment. This is due to the Mg... 2+ / F - Diffusion to the surface preferentially binds to MgF2. When the perovskite solution contacts MgF2, it triggers the reaction: MgF2 + H2O → Mg(OH)F + HF. Subsequently, Mg(OH)F reacts with PbI2: Mg(OH)F + PbI2 → Mg-O-Pb + HI + HF. This invention achieves the following technical effects through improved electron transport layer material: efficiency >24.5%, a 3% improvement compared to the single-doped system; device T80 >1200 h, excellent damp-heat stability; Mg-O bonds suppress oxygen vacancy generation; MgF... x O 2-x The buffer layer blocks I-migration; the flexible device has an efficiency of >22%, and the film is formed at 150℃ with excellent crystal orientation and no phase change at high temperature, and no pinholes appear.

[0027] In some embodiments, such as Figure 1 As shown, the perovskite solar cell further includes a first electrode, a perovskite light-absorbing layer (PVSK), a hole transport layer (HTL), and a second electrode, which are sequentially stacked to form a layered structure. The materials and thicknesses of the first electrode, perovskite light-absorbing layer (PVSK), hole transport layer (HTL), and second electrode are not limited; all commonly used materials are within the scope of this invention. The bandgap structure diagram is shown below. Figure 2As shown, the conduction band bottom of the electron transport layer (Mg:F-SnO2) is -3.92 eV, and the conduction band bottom of the perovskite light-absorbing layer is -3.7 eV, forming a "stepped" band arrangement. This allows photogenerated electrons to be efficiently extracted from the perovskite layer to the electron transport layer, while the 2.12 eV valence band shift effectively blocks the recombination of holes towards the electron transport layer side.

[0028] In some embodiments, the material of the first electrode is selected from at least one of ITO (indium tin oxide), FTO (fluorine-doped tin oxide), and AZO (aluminum-doped zinc oxide). The material of the first electrode can be any one or more of the above, preferably ITO glass. The material of the perovskite light-absorbing layer is selected from ABX3 and A2A. n-1 B n X 3n+1 The material of the hole transport layer is selected from at least one of the following: 1 ≤ n ≤ 10, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc.; A is selected from at least one of Cs, MA, and FA; B is selected from at least one of Pb and Sn; X is a halogen element, such as Cl, Br, I, etc. The material of the hole transport layer is selected from at least one of NiOx, V2O5, and MoO3. The material of the second electrode is selected from at least one of Ag, Au, and Cu, and the material of the second electrode can be any one or more of the above.

[0029] Furthermore, the thickness of the first electrode is 100 nm-200 nm, such as 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, etc.; the thickness of the electron transport layer is 10 nm-50 nm, such as 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc.; the thickness of the perovskite light-absorbing layer is 300 nm-800 nm, such as 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, etc.; the thickness of the hole transport layer is 50 nm-100 nm, such as 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.; and the thickness of the second electrode is 200 nm-400 nm, such as 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, etc. The thickness of each layer should preferably be within the above ranges to further improve the efficiency of the solar cell.

[0030] This invention also provides a method for fabricating a perovskite solar cell, comprising the following steps: S1, Preprocessing The first electrode (substrate) undergoes surface treatment to enhance hydrophilicity, and surface hydroxylation promotes film formation. The material of the first electrode is as described above in the instruction manual, with ITO glass being the preferred material.

[0031] In some embodiments, the pretreatment process includes: first, cleaning the substrate with a solvent to remove organic / inorganic contaminants; then, treating the substrate with ultraviolet ozone for 20-30 minutes to enhance hydrophilicity; and finally, treating it with O2 plasma for 2-5 minutes to hydroxylate the surface and promote film formation.

[0032] Furthermore, the type of solvent is not limited. For example, acetone, isopropanol, and deionized water can be used sequentially to ultrasonically clean the substrate for 10-20 minutes each to improve the removal effect of pollutants.

[0033] S2. Precursor solution for preparing the electron transport layer A precursor solution is obtained by reacting a tin salt, a solvent, an organomaglenoid source, a fluorine source, and an alcohol stabilizer. The solvent is an aqueous solution. During the reaction, tin undergoes hydrolysis to form [Sn3(OH)4]. 2+ The tin-oxygen cluster network at the core provides a uniform matrix for magnesium / fluorine doping; fluorine and magnesium complex to form a [Mg-F-Sn-O] bridging structure, enabling magnesium / fluorine to be atomically dispersed in the tin oxide lattice precursor.

[0034] In some embodiments, the process of preparing the precursor solution includes: mixing a tin salt and a solvent uniformly, then mixing with an organomagnesium source and sonicating until completely dissolved to obtain a mixed solution; adding an aqueous solution of a fluorine source dropwise to the mixed solution, followed by the addition of an alcohol stabilizer, reacting for 1-5 hours (e.g., 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, etc.), then filtering and storing in the dark. Adding the aqueous solution of the fluorine source dropwise is beneficial for controlling the reaction rate and preparing uniformly doped materials. The filtration method is not limited; for example, a PTFE membrane filter can be used, but it is not limited to this.

[0035] In some embodiments, the tin salt is selected from at least one of tin chloride, tin nitrate, tin sulfate, and tin acetylacetonate, and the tin salt can be any one or more of the above. The organic magnesium source is selected from at least one of Mg(CH3COO)2, magnesium acetylacetonate, magnesium citrate, and magnesium oxalate, and the organic magnesium source can be any one or more of the above. The fluorine source is selected from at least one of NH4F, ammonium bifluoride, and tetrabutylammonium fluoride, and the fluorine source can be any one or more of the above. The alcohol stabilizer is selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, diethylene glycol monomethyl ether, and propylene glycol methyl ether, and the alcohol stabilizer can be any one or more of the above.

[0036] To better control the doping ratio of fluorine and magnesium and ensure the total doping amount meets requirements, the inventors optimized the concentration and dosage ratio of the reagents used: In the mixed solution, the concentration of tin is 0.05 mol / L-0.2 mol / L (e.g., 0.05 mol / L, 0.10 mol / L, 0.15 mol / L, 0.20 mol / L, etc.), and the concentration of magnesium is 0.0005 mol / L-0.008 mol / L (e.g., 0.0005 mol / L, 0.0010 mol / L, 0.0030 mol / L, 0.0050 mol / L, 0.0080 mol / L, etc.); the concentration of fluorine in the added fluorine source aqueous solution is 0.1 mol / L-1... The concentration of tin and magnesium in the mixed solution is 1:(0.01-0.1), such as 1:0.01, 1:0.03, 1:0.05, 1:0.08, 1:0.10, etc., depending on the solvent concentration and volume of the fluorine source aqueous solution. This allows for better control of the final fluorine and magnesium doping ratio, thereby improving defect passivation and conductivity.

[0037] Adding alcohol stabilizers can prevent the carboxyl groups from undergoing excessively rapid coordination condensation with tin ions, thereby avoiding localized gelation and excessive growth of tin-oxygen clusters. To better utilize the effect of alcohol stabilizers, the molar ratio of tin salt to alcohol stabilizer should be controlled at 1:(0.5-2), such as 1:0.5, 1:1.0, 1:1.5, 1:2.0, etc.

[0038] In some embodiments, during the mixing process with the solvent, the mixing temperature is controlled at 35℃-50℃ (e.g., 35℃, 40℃, 45℃, 50℃, etc.), and the stirring time is 0.5h-3.0h (e.g., 0.5h, 1.0h, 2.0h, 3.0h, etc.) to achieve thorough mixing. The solvent can be a mixture of water and ethanol, with a volume ratio of water to ethanol of 1:(1.5-4), such as 1:1.5, 1:2.0, 1:2.5, 1:3.0, 1:3.5, 1:4.0, etc. Using a mixture of water and ethanol allows for precise control of the balance between tin salt hydrolysis and colloidal stability, thereby obtaining a homogeneous, stable precursor solution with excellent film-forming properties.

[0039] Furthermore, when mixing with an organomagnesium source and undergoing ultrasonic treatment, the ultrasonic temperature should be controlled at 50℃-70℃, such as 50℃, 55℃, 60℃, 65℃, 70℃, etc., and the ultrasonic time is unlimited, such as about 30 minutes, until complete dissolution is achieved. The dropping rate of the aqueous solution of the fluorine source is 0.5mL / min-1.5mL / min, such as 0.5mL / min, 1.0mL / min, 1.5mL / min, etc.

[0040] S3, Fabrication of the electron transport layer The precursor solution obtained in step S2 is coated onto the first electrode, followed by annealing to form a magnesium and fluorine co-doped tin oxide film.

[0041] In some embodiments, the precursor solution is spin-coated onto the first electrode, followed by annealing. The annealing temperature is controlled at 120℃-150℃, such as 120℃, 130℃, 140℃, 150℃, etc.; the annealing time is 20min-60min, such as 20min, 30min, 40min, 50min, 60min, etc. The preparation method provided by this invention can form a film at 150℃, with excellent crystal orientation and no phase transition at high temperatures, which can meet the application requirements of flexible devices.

[0042] Furthermore, the annealing process is carried out in an air atmosphere, with the heating rate controlled at 4℃ / s-6℃ / s, such as 4℃ / s, 5℃ / s, 6℃ / s, etc.

[0043] In other embodiments, an external buffer layer scheme can also be used, such as magnetron sputtering of MgF2, with precise thickness control. However, the external buffer layer requires additional equipment, vacuum equipment is expensive, and Mg-O-Pb bonds cannot be formed.

[0044] S4. Fabrication of perovskite solar cells with stacked structures A perovskite light-absorbing layer (PVSK), a hole transport layer (HTL), and a second electrode are sequentially fabricated on the electron transport layer to form a structure as shown in the figure. Figure 1 The layered structure shown above specifies the material and thickness of each layer, as described in the instruction manual.

[0045] In some embodiments, the process of preparing the perovskite light-absorbing layer includes: preparing materials according to the composition of the perovskite light-absorbing layer, such as dissolving raw materials such as CsBr, PbI2, FAI, FABr, and MACl in a solvent in a certain proportion to obtain a perovskite precursor solution; then, coating the perovskite precursor solution onto the electron transport layer, adding an anti-solvent during spin coating, followed by high-temperature annealing, controlling the annealing temperature to be 100℃-120℃, such as 100℃, 110℃, 120℃, etc.; and annealing time to be 15min-30min, such as 15min, 20min, 30min, etc.

[0046] The solvent used is not limited; for example, a mixture of DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide) can be used. When preparing the perovskite precursor solution, heating and stirring can be used to promote dissolution, such as at a temperature of 50℃-70℃. The perovskite precursor solution can be spin-coated onto the electron transport layer, with a spin-coating speed of 2000-4000 rpm / min and a spin-coating time of 20 s-40 s. Chlorobenzene is added dropwise as an anti-solvent at the 10th-30th second.

[0047] In some embodiments, a hole transport layer can be deposited using PVD, and the material of the hole transport layer is as described above. The second electrode can be fabricated using vapor deposition, specifically an Ag electrode.

[0048] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0049] Example 1 This invention also provides a method for fabricating a perovskite solar cell, comprising the following steps: (1) Pretreatment A 150 nm thick ITO glass substrate was used as the base material. The substrate was ultrasonically cleaned for 15 minutes each with acetone, isopropanol, and deionized water to remove organic / inorganic contaminants. The substrate was then treated with ultraviolet ozone for 25 minutes to enhance hydrophilicity. Finally, O2 plasma treatment for 3 minutes was applied to the surface for hydroxylation, promoting film formation.

[0050] (2) Preparation of precursor solution for electron transport layer Add 0.1M SnCl2·2H2O to a water-ethanol mixed solvent (water to ethanol volume ratio of 1:2.3) and stir magnetically at 40℃ for 1h; add Mg(CH3COO)2 (1.5 at%) and sonicate at 60℃ for 30min until completely dissolved to obtain a mixed solution with a total volume of 100mL. The concentration of tin in the mixed solution is 0.1 mol / L and the concentration of magnesium is 0.0015 mol / L.

[0051] Add 0.5 mol / L NH4F aqueous solution dropwise to the mixed solution (the volume added should be such that the molar ratio of magnesium to fluorine meets the chemical formula requirements, the same below), at a dropping rate of 1 mL / min; after the addition is complete, add ethylene glycol methyl ether, controlling the molar ratio of SnCl2·2H2O to ethylene glycol methyl ether to be 1:1, stir at 1200 rpm for 2 h, filter with a 0.22 μm PTFE filter membrane, and store in the dark.

[0052] (3) Fabrication of electron transport layer The precursor solution obtained in step (2) was spin-coated onto an ITO glass substrate at a speed of 3000 rpm for 30 s with an acceleration of 1000 rpm / s. Then, it was annealed at high temperature in air at a heating rate of 5℃ / s for 30 min at 135℃.

[0053] The chemical formula of the prepared electron transport layer is Sn. 0.985 Mg 0.015 O 1.97 F 0.03 .

[0054] (4) Fabrication of perovskite solar cells with stacked structures Deposition of perovskite light-absorbing layer: Raw materials such as CsBr, PbI2, FAI, FABr, and MACl are mixed in a specific ratio (target chemical formula is CsBr). 0.1 FA 0.9 PbBr 0.05 I 0.95 The perovskite precursor solution was dissolved in a mixed solvent of DMF and DMSO (total volume 1 mL, DMF to DMSO volume ratio 4:1) at 60℃ with stirring. The solution was heated and stirred to form a perovskite precursor solution. The spin coating speed was set to 3000 rpm / min and the spin coating time was 30 s. Chlorobenzene antisolvent (100 μL) was added dropwise at the 20th second. After spin coating, the solution was annealed at 110℃ for 20 min to form a perovskite polycrystalline thin film.

[0055] Hole transport layer (HTL) deposition using PVD technology: NiO is deposited on the surface of the perovskite layer using the PVD method. X The thin film has a hole transport layer thickness of 80 nm.

[0056] Ag electrodes were prepared by metal evaporation: a silver Ag electrode with a thickness of 300 nm was deposited on the hole transport layer by vacuum thermal evaporation.

[0057] Example 2 The only difference from Example 1 is that in step (2), the amounts of Mg(CH3COO)2 and NH4F aqueous solution are changed, so that the chemical formula of the electron transport layer prepared in step (3) is Sn. 0.99 Mg 0.01 O 1.98 F 0.02 .

[0058] Example 3 The only difference from Example 1 is that in step (2), the amounts of Mg(CH3COO)2 and NH4F aqueous solution are changed, so that in step (3), the chemical formula of the electron transport layer prepared is Sn. 0.97Mg 0.03 O 1.96 F 0.04 .

[0059] Example 4 The only difference from Example 1 is that in step (2), the amounts of Mg(CH3COO)2 and NH4F aqueous solution are changed, so that in step (3), the chemical formula of the electron transport layer prepared is Sn. 0.985 Mg 0.015 O 1.96 F 0.04 .

[0060] Comparative Example 1 Using undoped tin oxide as the ETL layer, steps (2) and (3) are modified as follows: In step (2), 0.1 MSnCl2·2H2O is added to a water-ethanol mixed solvent (the volume ratio of water to ethanol is 1:2.3), and the mixture is magnetically stirred at 40°C for 1 h to obtain a clear and transparent SnO2 precursor solution. The total volume of the mixed solution is 100 mL, and the concentration of tin is 0.1 mol / L. In step (3), the precursor solution obtained in step (2) is spin-coated onto an ITO glass substrate at a speed of 3000 rpm for 30 s with an acceleration of 1000 rpm / s. Then, high-temperature annealing is performed in an air atmosphere at a heating rate of 5°C / s, and annealing is carried out at 135°C for 30 min to obtain an undoped SnO2 electron transport layer.

[0061] Comparative Example 2 Using F doping - Tin oxide is used as the ETL layer. Steps (2) and (3) are modified as follows: In step (2), 0.1 MSnCl2·2H2O is added to a water-ethanol mixed solvent (the volume ratio of water to ethanol is 1:2.3), and the mixture is magnetically stirred at 40°C for 1 h; 5 mL of 0.5 mol / L NH4F aqueous solution is added dropwise to the mixed solution at a dropping rate of 1 mL / min; after the addition is complete, ethylene glycol methyl ether is added, and the molar ratio of SnCl2·2H2O to ethylene glycol methyl ether is controlled to be 1:1. The mixture is stirred at 1200 rpm for 2 h, filtered with a 0.22 μm PTFE filter membrane, and stored in the dark. The total volume of the mixed solution is 100 mL, and the concentration of tin is 0.1 mol / L. In step (3), the precursor solution obtained in step (2) is spin-coated onto an ITO glass substrate at a speed of 3000 rpm for 30 s, with an acceleration of 1000 rpm / s. Then, high-temperature annealing was performed in air at a heating rate of 5℃ / s, and annealing was carried out at 135℃ for 30 min to obtain an F-doped SnO2 electron transport layer with the chemical formula SnO. 1.97 F 0.03 .

[0062] Comparative Example 3 Using Mg 2+ Using tin oxide as the ETL layer, steps (2) and (3) are modified as follows: In step (2), 0.1 MSnCl2·2H2O is added to a water-ethanol mixed solvent (the volume ratio of water to ethanol is 1:2.3), and the mixture is magnetically stirred at 40°C for 1 h; Mg(CH3COO)2 (1.5 at%) is added, and the mixture is sonicated at 60°C for 30 min until completely dissolved to obtain a mixed solution. The total volume of the mixed solution is 100 mL, the concentration of tin is 0.1 mol / L, and the concentration of magnesium is 0.0015 mol / L. Subsequently, ethylene glycol methyl ether is added, and the molar ratio of SnCl2·2H2O to ethylene glycol methyl ether is controlled at 1:1. The mixture is stirred at 1200 rpm for 2 h, filtered through a 0.22 μm PTFE membrane, and stored in the dark. In step (3), the precursor solution obtained in step (2) was spin-coated onto an ITO glass substrate at a speed of 3000 rpm for 30 s with an acceleration of 1000 rpm / s. Then, it was annealed at high temperature in air at a heating rate of 5℃ / s for 30 min at 135℃ to obtain a Mg-doped SnO2 electron transport layer with the chemical formula Sn. 0.985 Mg 0.015 O2.

[0063] Comparative Example 4 Using Li + / F - Co-doped tin oxide is used as the ETL layer. Steps (2) and (3) are modified as follows: In step (2), 0.1 M SnCl2·2H2O is added to a water-ethanol mixed solvent (the volume ratio of water to ethanol is 1:2.3), and the mixture is magnetically stirred at 40°C for 1 h; LiCl (1.5 at%) is added, and the mixture is sonicated at 60°C for 30 min until it is completely dissolved to obtain a mixed solution; 5 mL of 0.5 mol / L NH4F aqueous solution is added dropwise to the mixed solution at a dropping rate of 1 mL / min; after the addition is complete, ethylene glycol methyl ether is added, and the molar ratio of SnCl2·2H2O to ethylene glycol methyl ether is controlled at 1:1. The mixture is stirred at 1200 rpm for 2 h, filtered through a 0.22 μm PTFE filter membrane, and stored in the dark. The total volume of the mixed solution is 100 mL, the concentration of tin is 0.1 mol / L, and the concentration of lithium is 0.0015 mol / L. In step (3), the precursor solution obtained in step (2) is spin-coated onto an ITO glass substrate at a speed of 3000 rpm for 30 s with an acceleration of 1000 rpm / s. Then, it is annealed at high temperature in air at a heating rate of 5℃ / s for 30 min at 135℃ to obtain a Li / F co-doped SnO2 electron transport layer with the chemical formula Sn.0.985 Li 0.015 O 1.97 F 0.03 .

[0064] Experimental Example 1 The performance of the perovskite solar cells prepared in the examples and comparative examples was tested using conventional methods, and the results are shown in Table 1.

[0065] Table 1 Performance parameters of solar cell devices

[0066] It can be seen that the examples use Mg 2+ With F - The co-doped SnO2ETL system can significantly improve battery performance compared to the comparative system.

[0067] Comparative Example 4 uses Li + / F - Co-doping significantly improves conductivity, but Li + Easy to migrate (efficiency decreases by 30% after aging at 85℃).

[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A perovskite solar cell, characterized in that, It includes an electron transport layer comprising a magnesium and fluorine co-doped tin oxide film.

2. The perovskite solar cell according to claim 1, characterized in that, The chemical formula of the magnesium and fluorine co-doped tin oxide film is Sn. 1-x Mg x O 2-y F y Where 0.005≤x≤0.04, 0.01≤y≤0.06, and the molar ratio of Mg to F is 1:(1.5-3.0).

3. The perovskite solar cell according to claim 1 or 2, characterized in that, It also includes a first electrode, a perovskite light-absorbing layer, a hole transport layer and a second electrode, and the first electrode, the electron transport layer, the perovskite light-absorbing layer, the hole transport layer and the second electrode are stacked sequentially to form a stacked structure; Preferably, a buffer layer with the chemical formula MgF is further included between the perovskite light-absorbing layer and the tin oxide film. x O 2-x ; Preferably, in the tin oxide film, Mg 2+ Filling Sn vacancies increases the oxygen vacancy formation energy from 1.6–2.0 eV to 2.5–3.5 eV; F - Replace O 2- Provides free electrons, with an electron mobility of up to 30 cm⁻¹ 2 / V·s or more; Preferably, Mg inhibits lattice expansion caused by F, the lattice distortion energy is <0.05 eV, and no cracks are generated; Preferably, co-doping shifts the SnO2 conduction band from -4.03~-3.98 eV to -3.95~-3.90 eV, resulting in a mismatch of <0.02 eV with the perovskite energy level and increasing the open-circuit voltage Voc to 1.15~1.20 V.

4. The perovskite solar cell according to claim 3, characterized in that, The material of the first electrode is selected from at least one of ITO, FTO and AZO; And / or, the material of the perovskite light-absorbing layer is selected from ABX3 and A2A. n-1 B n X 3n+1 At least one of the following, wherein 1≤n≤10, A is selected from at least one of Cs, MA and FA; B is selected from at least one of Pb and Sn; X is a halogen element; And / or, the material of the hole transport layer is selected from at least one of NiOx, V2O5 and MoO3; And / or, the material of the second electrode is selected from at least one of Ag, Au and Cu; And / or, the thicknesses of the first electrode, the electron transport layer, the perovskite light-absorbing layer, the hole transport layer, and the second electrode are, respectively, 100nm-200nm, 10nm-50nm, 300nm-800nm, 50nm-100nm, and 200nm-400nm.

5. A method for preparing a perovskite solar cell according to any one of claims 1-4, characterized in that, include: Preparation of precursor solution: A tin salt, solvent, organomagnesium source, fluorine source and alcohol stabilizer are mixed and reacted to obtain a precursor solution; Preparation of electron transport layer: The precursor solution is coated on the first electrode and then annealed.

6. The preparation method according to claim 5, characterized in that, The process of preparing the precursor solution includes: mixing the tin salt and the solvent, then mixing with the organomagnesium source and sonicating until completely dissolved to obtain a mixed solution; adding an aqueous solution of fluorine source dropwise to the mixed solution, and after the addition is complete, adding the alcohol stabilizer, reacting for 1 h-5 h, and then filtering; And / or, spin-coating the precursor solution onto the first electrode, followed by annealing, controlling the annealing temperature at 120℃-150℃ and the annealing time at 20 min-60 min.

7. The preparation method according to claim 6, characterized in that, In the mixed solution, the concentration of tin is 0.05 mol / L-0.2 mol / L, and the concentration of magnesium is 0.0005 mol / L-0.008 mol / L; the concentration of fluorine in the added aqueous solution of the fluorine source is 0.1 mol / L-1 mol / L, and the volume ratio of the mixed solution to the aqueous solution of the fluorine source is 1:(0.01-0.1). And / or, the tin salt is selected from at least one of tin chloride, tin nitrate, tin sulfate, and tin acetylacetonate; And / or, the organic magnesium source is selected from at least one of Mg(CH3COO)2, magnesium acetylacetonate, magnesium citrate, and magnesium oxalate; And / or, the fluorine source is selected from at least one of NH4F, ammonium bifluoride, and tetrabutylammonium fluoride; And / or, the alcohol stabilizer is selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, diethylene glycol monomethyl ether and propylene glycol methyl ether, and the molar ratio of the tin salt to the alcohol stabilizer is 1:(0.5-2).

8. The preparation method according to claim 6, characterized in that, During the mixing process with the solvent, the mixing temperature is controlled at 35℃-50℃, and the stirring time is 0.5 h-3.0 h; And / or, the solvent is a mixture of water and ethanol, wherein the volume ratio of water to ethanol is 1:(1.5-4). And / or, during the ultrasonic treatment, the ultrasonic temperature is controlled to be 50℃-70℃; And / or, the dropping rate of the aqueous solution of the fluorine source is 0.5 mL / min to 1.5 mL / min; And / or, the annealing process is carried out in an air atmosphere, with the heating rate controlled at 4℃ / s-6℃ / s.

9. The preparation method according to claim 5, characterized in that, Also includes: A perovskite light-absorbing layer, a hole transport layer, and a second electrode are sequentially fabricated on the electron transport layer to form a stacked structure.

10. The preparation method according to claim 9, characterized in that, The process of preparing the perovskite light-absorbing layer includes: preparing the ingredients according to the composition of the perovskite light-absorbing layer and mixing and dissolving them with a solvent to form a perovskite precursor solution; applying the perovskite precursor solution onto the electron transport layer; adding an anti-solvent during spin coating; and then annealing at high temperature, controlling the annealing temperature to be 100℃-120℃ and the annealing time to be 15min-30min. And / or, the hole transport layer is deposited using PVD; And / or, the second electrode is prepared by vapor deposition.